Democratization and De-democratization Paths in Ecuador’s Communications - Ramos, Isabel (2013)
Starting from the fact that politics in Ecuador have historically generated the legal and material conditions necessary for an accentuated de-democratization of communications in this country, this article analyzes the “state activism” carried out by Rafael Correa’s administration regarding mass media. Instead of assuming that this activism –which is implemented by a political regime with populist qualities– necessarily leads to democratization of media communications, this article recognizes its accomplishments and takes caution on governmental actions that have resulted in a loss of democratic exercise.